2018
DOI: 10.1007/s11356-017-0854-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzene reduction using nanoscale zero-valent iron supported by polystyrene microspheres with different surface functional groups

Abstract: Three polystyrene (PS) resin microspheres supported nanoscale zero-valent iron (nZVI), i.e., nZVI@PS, nZVI@PS-Cl, and nZVI@PS-N, were prepared and characterized by FT-IR, XPS, SEM, EDS, and weighing method. The functional groups on the carriers showed obvious influence on the loading quantity, the micro morphology, and the reduction efficiency of these supported nZVI. The best hybrid reducer was nZVI@PS-N. The load quantity of nZVI was 0.2476 g/g, and some of them were dispersed and the others remained as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Studies have shown that nZVI can efficiently activate persulfate. Li et al [57]activated PS by nZVI to remove nitrobenzene, the results found that higher temperature and acidic conditions are more conducive to the removal of nitrobenzene, and the removal rate can reach 99%. Wu et al [58] used nanoscale zero-valent iron supported on the organo-montmorillonite composite to activate PS, and the degradation rate of sulfamethazine can reach 97% within ten minutes.…”
Section: Indirect Effect Of Persulfate Activated By Nzvimentioning
confidence: 99%
“…Studies have shown that nZVI can efficiently activate persulfate. Li et al [57]activated PS by nZVI to remove nitrobenzene, the results found that higher temperature and acidic conditions are more conducive to the removal of nitrobenzene, and the removal rate can reach 99%. Wu et al [58] used nanoscale zero-valent iron supported on the organo-montmorillonite composite to activate PS, and the degradation rate of sulfamethazine can reach 97% within ten minutes.…”
Section: Indirect Effect Of Persulfate Activated By Nzvimentioning
confidence: 99%
“…Polystyrene is a major material type in microplastics, and it has a stronger sorption capacity for aromatic compounds due to π–π interactions [ 30 , 31 ]. The surface of polystyrene is hydrophobic and contains a relatively large number of active aromatic sites that allow π–π interactions between aromatic rings to take effect, which means that the aromatics pollutants, such as nitroaromatics and azo-dyes in water should be easily adsorbed by polystyrene carriers [ 32 ]. Juan Wang [ 33 ] found that polystyrene can accumulate phenanthrene, nitrobenzene, and naphthalene in water.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polystyrene microplastics had a size effect on the adsorption of phenanthrene and nitrobenzene [ 34 ]. Moreover, the polystyrene microspheres loaded zero-valent iron had good potential application in the reductive degradation and emergency rescue of nitrobenzene contamination [ 32 ]. However, it is inconvenient to separate polystyrene from the emulsion after polymerization for its small size.…”
Section: Introductionmentioning
confidence: 99%